Bibliometric Mapping Analysis of Scientific Publications in Chemistry Field on Cerium Oxide Nanoparticles Using Vosviewer - Anisa Klarasita; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (JSEP (Journal of Science Education and Practice), 2022)
This study aims to look at the advancement of scientific publications related to cerium oxide nanoparticles through a bibliometric approach using qualitative methods with descriptive statistics on literature studies on scientific articles. Two types of software are used: Publish or Perish and VOSviewer. Publish or Perish is used as a source to search for various relevant articles through the Google Scholar database, using the keyword "Cerium Oxide Nanoparticle," and obtained 997 articles from 2012 to 2022. The results show that 2012 and 2013 were fairly constant, increasing from 2014 to 2016, fluctuating from 2017 to 2020, and decreasing in 2021 and 2022. Data from Publish or Perish is inputted into VOSviewer to visualize and analyze mapping trends related to cerium oxide nanoparticles, obtaining 7 clusters of 189 items. The popularity of the terms used in scientific publications related to cerium oxide nanoparticles during the last three years has become less trending. This study concludes that there are still opportunities for future researchers to develop or even make discoveries related to cerium oxide nanoparticles.